Motor proficiency and preacademic learning in the young child. - Feder, Katya P. (University of Ottawa (Canada), 1993)
Children with learning difficulties often demonstrate a decreased level of motor proficiency. Researchers have identified learning disability subtypes and discovered a link between math-related learning difficulties and perceptual-motor, spatial and organizational deficits. Learning difficulties are typically not diagnosed until the middle primary grades following repeated academic failure, however clumsiness, which has also been linked to difficulties with academic learning, can often be detected earlier. The purpose of this study was to examine the relationship between motor proficiency and preacademic difficulties in the young child; specifically the relationship between early development of visual spatial skills, sequencing and arithmetic ability. Fifty children, ages 4 years 3 months to 5 years 8 months, were tested during two 30-40 minute sessions using: (1) the Miller Assessment for Preschoolers (MAP), a screening test designed to identify children at-risk for learning difficulties; (2) a pursuit tracking task (Buck, Leonardo & Hyde, 1981); (3) number/counting concept items (Miller, 1990). Subjects were divided into high and low performance groups based on total MAP score, specified MAP spatial items and number/counting concept items, and their performance on the pursuit tracking task examined.
Keywords: Health Sciences, Human Development.